Pembelajaran Ansambel Musik di Kelas IX SMP YTKA Solok Selatan - Andri Ahmat Yani; Jagar Lumbantoruan (SENDRATASIK UNP, 2023)
Cultural Arts Learning at the secondary education level is carriedout according to the 2013 curriculum. One of the content of the lesson is a simple or similar ensemble. The subject matter given by the teacher to students at SMP YTKA  South Solok  is a rekorder ensemble. Teacher preparation is designed in accordance  with the design  of the implementation of learning to be carried out in the classroom. Rekorder ensamble learning is carried out weekly in the ninth grade of YTKA Junior High School with the target of students being skilled at playing ensambles.However, after the lesson ended, the targets planned by the teacher and the students were not as expected. The purpose of this study was was to identify and describe the learning  of rekorder  music ensembles in the ninth grade of SMP YTKA South Solok. This type of research is a qualitative research approach with descriptive analysis method. Data collection techniques are literature study, observasion, interviews, and document studies. Data analysis techniques are identifying, classifying, clarifying, interpreting, describing and concluding. The results of the research  that were obtained were related  to the learning of rekorder ensembles in the ninth grade of SMP YTKA South Solok namely: (1) the design of the lesson  plan was prepared according to the existing components. The formulation of learning objectives  does not cover the cognitive, affective, and psychomotor domains, (2) the implementation of learning regarding teacher activities is not in accordance with the learning stages because in the initial activities, the teacher does not convey the topic and learning objectives, and does not review the students’ initial abilities in relation to playing rekorders. In the core part of learning , the teacher dominates learning by explaining  without example and demonstration about rekorder ensambles. Independent activities are carried out by students individually and do not receive teacher guidance. The impact of the recording ansambeles learning process, student learning  outcomes about the rekorder ensamble practice have not been achieved properly.